An Effective and Efficient Implementation of OBE Framework within Constrained Pakistani Environment to Attain Desired Learning Outcomes - Ashab Mirza; Saba Javed (Sir Syed University Research Journal of Engineering and Technology, 2022)
Outcome-based-education (OBE) is an educational theory that bases each part of an educational system around goals (outcomes). Pakistan Engineering Council (PEC) introduced the OBE in Pakistani engineering higher-education-institutions (HEIs),from 2018, in the replacement of previously followed Syllabus& Curriculum based education system. Key to success of OBE System is its continuous-quality-improvement (CQI) mechanism. The CQI mechanism design should be based on accurate assessment process and flawless evaluation of OBE System parameters; otherwise the OBE System’s benefits cannot be achieved. However, some HEIs have not devised an effective CQI mechanism and they still using classical procedures and academic tools in implementation of the OBE Framework, which cannot give desired results from the new System. This paper presents that; instead of presently employed loose-control, a modified stringent control strategy for academic activity and employment of latest technology, can make the CQI mechanism, more effective and efficient. This paper therefore presents a two-fold contribution. At first, the implementation problems of the OBE System are critically analyzed. Secondly, few modifications in the existing approaches have been introduced to achieve the desired results from the recently adopted OBE system.